Glycinergic Modulation of Pain in Behavioral Animal Models - Peiser-Oliver, Julian M.; Evans, Sally; Adams, David J.; Christie, Macdonald J.; Vandenberg, Robert J.; Mohammadi, Sarasa A. (Frontiers in Pharmacology, 2022)
Animal models of human pain conditions allow for detailed interrogation of known and hypothesised mechanisms of pain physiology in awake, behaving organisms. The importance of the glycinergic system for pain modulation is well known, however, manipulation of this system to treat and alleviate pain has not yet reached the sophistication required for the clinic. Here, we review the current literature on what animal behavioural studies have allowed us to elucidate about glycinergic pain modulation, and the progress toward clinical treatments so far. First, we outline the animal pain models that have been used, including nerve injury models for neuropathic pain, chemogenic pain models for acute and inflammatory pain, and other models that mimic painful human pathologies such as diabetic neuropathy. We then discuss the genetic approaches to animal models that have identified the crucial glycinergic machinery involved in neuropathic and inflammatory pain. Specifically, two glycine receptor (GlyR) subtypes, GlyRα1(β) and GlyRα3(β), and the two glycine transporters (GlyT), GlyT1 and GlyT2. Finally, we review the different pharmacological approaches to manipulating the glycinergic system for pain management in animal models, including partial vs full agonism, reversibility, and multi-target approaches. We discuss the benefits and pitfalls of using animal models in drug development broadly, as well as the progress of glycinergic treatments from pre-clinical to clinical trials.